A "graça" no campo da religião : uma análise retórica da pregação de Cláudio Duarte - Freitas, Franciely Corrêa de (2017)
The field of religion tends to be characterized by a tone of seriousness, not humor. Perceiving the presence and a dissemination of humor in a religious social practice, case of preaching, which deals with matters related to the sacred and therefore considered serious, was the main motivation for the realization of this dissertation. In this sense, this research aims to investigate the role and relevance of humor in the religious preaching "Reconstructing the truths of God", pronounced by the pastor Cláudio Duarte. The hypothesis is that humor is extremely important in preaching, since it has the function of contributing to the effectiveness of the persuasive process. The theoretical apparatuses that support this study are from the Aristotelian rhetoric (ARISTÓTELES, 2000; 2011), the New Rhetoric (PERELMAN, OLBRECHTS-TYTECA, 2005, REBOUL, 2004; MEYER, 2007; FERREIRA, 2010), of theorists who address issues of humor (TRAVAGLIA, 1992; BERGSON, 2007; PROPP, 1992; PERELMAN; OLBRECHTS-TYTECA, 2005; CARMELINO, 2009; 2012) of the field of religion (CITELLI, 2005; NASCIMENTO, 2012; FIGUEIREDO; RODRIGUES, 2008) and the preaching genre (FIGUEIREDO et al., 2009). The analysis allowed us to verify some humor production techniques used in more recurrent way, in the case of the communion allusion figure, the arguments of contradiction and incompatibility, reciprocity, comparison, and the pragmatic. Besides that, the lexical choices and the prosodic elements were of great relevance for the argumentation and the construction of the humor. It was also possible to observe that, through the logos, the speaker constructs the image (ethos) of serious, informed, leader, irreverent and humble, besides moving passions (pathos), as calm, love, compassion, joy, confidence and a fear. In this way, the humor present in the preaching of Duarte is not used in an unpretentious way; In fact, it is a resource that contributes in an efficient way to the speaker's speech in order to achieve audience support.